A mobile measure device for the analysis of highly dynamic movement techniques - Jaitner, T.; Gawin, W. (Procedia Engineering, 2010)
A mobile measure device was developed to analyze the smash in Badminton. Kinematic data of the arm and the racket were measured by inertial sensors, stored and transferred via Wi-Fi. Data of 26 Badminton players were collected. Additionally, the shuttle velocity was determined by high-speed video analysis. The resultant racket acceleration showed highest correlation with the ball velocity (r=,84). Differences between international and national players were observed in the means and standard deviations of the racket acceleration and in the negative acceleration of the lower arm. It is suggested that an abrupt stopping of the lower arm supports the generation of high racket acceleration.